Regulation of Electronic Communications Market - Gjika, Jonida (European Journal of Multidisciplinary Studies, 2016)
The field of electronic communications for the importance of the everyday life, and the impact that reflects the economic development, it is considered important, so that the approach to electronic communications services has found attention from state structures in each country, consequently in Albania. Its electronic communications market operates on the basis of a special material law, under the supervision and continuous monitoring of the regulatory entity (AEPC), who fulfills his regulatory mission through ex-ante intervention in the market, as well as attention and legal responsibility over those of the Competition Authority which extend its effects through ex post interventions. The structure of the market for the (number and dimensions of the players) in order to successfully fulfill the regulatory mission it should not be a political objective, but to be finalized in concrete results. Political objectives focused on innovation and technological innovation, to increase investment, expanding opportunities for consumer choice, in terms of competitive prices for market products /services, which ultimately serve for the final goal of the regulator to maximize social welfare, are provided to only as a combination of regulatory measures and legal instruments to achieve those objectives, through the use of appropriate models for market regulation as a first step to target the achievement of effective and comprehensive competition, and measuring the performance of the markets in which regulation orients in a competitive market dynamic.